VEZF1–guanine quadruplex DNA interaction regulates alternative polyadenylation and detyrosinase activity of VASH1 - Li, Lin (Nucleic Acids Res, 2020)
Vascular endothelial zinc finger 1 (VEZF1) plays important roles in endothelial lineage definition and angiogenesis. Vasohibins 1 and 2 (VASH1 and VASH2) can form heterodimers with small vasohibin-binding protein (SVBP) and were recently shown to regulate angiogenesis by acting as tubulin detyrosinases. Here, we showed that VEZF1 binds directly with DNA guanine quadruplex (G quadruplex, G4) structures in vitro and in cells, which modulates the levels of the two isoforms of VASH1 mRNA. Disruption of this interaction, through genetic depletion of VEZF1 or treatment of cells with G4-stabilizing small molecules, led to increased production of the long over short isoform of VASH1 (i.e. VASH1A and VASH1B, respectively) mRNA and elevated tubulin detyrosinase activity in cells. Moreover, disruption of VEZF1-G4 interactions in human umbilical vein endothelial cells resulted in diminished angiogenesis. These results suggest that the interaction between VEZF1 and G4 structures assumes a crucial role in angiogenesis, which occurs through regulating the relative levels of the two isoforms of VASH1 mRNA and the detyrosinase activity of the VASH1-SVBP complex. Together, our work revealed VEZF1 as a G4-binding protein, identified a novel regulatory mechanism for tubulin detyrosinase, and illustrated that the VEZF1- and VASH1-mediated angiogenesis pathways are functionally connected.